Hasmonean Jerusalem in the Light of Archaeology Notes on Urban Topography - Geva, Hillel (Journal of Hellenistic Pottery and Material Culture, 2018)
The fortified area of late First Temple period Jerusalem encompassed the City of David, the Ophel and the Temple Mount on the eastern ridge, and for the first time the large area of the south-western hill as well. During the Persian period the area of Jerusalem was once more reduced to its earlier boundaries and confined to the eastern ridge. The city remained in these boundaries during the Early Hellenistic period. In the 2nd century BCE, settlement began on the south-western hill. Only with the establishment Hasmonean rule in Jerusalem in the mid-2nd century BCE did conditions emerge to allow expansion to this hill, which was eventually fortified by the First Wall.